2006
DOI: 10.1007/s11936-006-0043-5
|View full text |Cite
|
Sign up to set email alerts
|

Congenital long QT syndrome: Diagnosis and management in pediatric patients

Abstract: The long QT syndrome (LQTS) is characterized by electrocardiographic abnormalities and a high incidence of syncope and sudden cardiac death (SCD). The diagnosis is suggested when ventricular repolarization abnormalities result in prolongation of the corrected QT interval. When LQTS is suspected, genetic screening may identify a specific long QT subtype and provide guidance for appropriate therapy. Treatment depends on the relative risk of SCD, which is increased with longer QT durations, prior cardiac events, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…We also found that propranolol, a b-receptor blocker, decreases susceptibility to VF, relating to its suppression of antioxidant activity (Anderson et al 1996) and other pro-inflammatory factors that lead to abnormal expression of ERG protein in the myocardium. This is consistent with previous reports that propranolol can be used to treat LQTS (Bar-Cohen & Silka 2006;Hobbs et al 2006).…”
Section: Over-expression Of Erg Proteinsupporting
confidence: 93%
“…We also found that propranolol, a b-receptor blocker, decreases susceptibility to VF, relating to its suppression of antioxidant activity (Anderson et al 1996) and other pro-inflammatory factors that lead to abnormal expression of ERG protein in the myocardium. This is consistent with previous reports that propranolol can be used to treat LQTS (Bar-Cohen & Silka 2006;Hobbs et al 2006).…”
Section: Over-expression Of Erg Proteinsupporting
confidence: 93%
“…Congenital coronary artery anomalies Absence of specific findings or ischaemic findings 22,24 Kawasaki disease QRS amplitude changes: increased S wave depth in V1, increased R wave height in V6, increased Q wave depth in V6; Increased QT dispersion 174 Hypertrophic cardiomyopathy Pathological Q waves and repolarisation abnormalities; Increased left ventricular voltage 30 Arrhythmogenic right ventricular dysplasia T-wave inversion in V3; QRS ⩾ 110 ms in V1-V2-V3; Right bundle branch block; epsilon wave (arrow); frequent premature ventricular complexes with left bundle branch block morphology 175,176 LQT syndrome QTc ⩾480 ms; biphasic contour or prominent notch in the T wave; T-wave morphologic alterations; alternating T-wave morphology. [177][178][179] LQT1: broad T wave; LQT2: lowamplitude T wave; LQT3: long isoelectric ST segment Short QT syndrome QTc < 320 ms; short or absent ST segment; tall, narrow, and peaked T-waves 75,77,180 Catecholaminergic polymorphic ventricular tachycardia…”
Section: Conditionmentioning
confidence: 99%
“…[3][4][5][6] Whether these events are due to inherent limitations of ␤-blocker or avoidable factors is unknown. Implantable cardioverter-defibrillators (ICDs) are being used increasingly in LQTS patients, and these "failures" are used to justify implantation in patients without a cardiac arrest and even as initial therapy, including in children and teenagers in whom ICDs produce many complications [7][8][9][10] and impair quality of life without always preventing sudden death. 8,11,12 …”
mentioning
confidence: 99%